Կ. Պոլսի և Զմյուռնիայի հայ ազգաբնակչության տեղահանումների շուրջ (1915–1916 թթ.) - Ալբերտ Խառատյան (ՀՀ ԳԱԱ հրատ.)
Депортация армян Константинополя и Смирны не имела массового характера и в основном была обусловлена внешнеполитическими причинами. During the Armenian Genocide the Young Turks started the deportation of the Armenians from Constantinople on April 24 1915, when thousands of thinkers, party leaders, priests and others were arrested in a few weeks.
Keywords: History; Armenian Genocide (1915); D History